2017
DOI: 10.1002/hep.29350
|View full text |Cite
|
Sign up to set email alerts
|

Role of ErbB/HER family of receptor tyrosine kinases in cholangiocyte biology

Abstract: The ErbB/HER family comprises four distinct tyrosine kinase receptors, EGFR/ErbB1/HER1, ErbB2/HER2, ErbB3/ HER3, and ErbB4/HER4, which trigger intracellular signals at the origin of essential cellular functions, including differentiation, proliferation, survival, and migration. Epithelial cells, named cholangiocytes, that line intrahepatic and extrahepatic bile ducts, contribute substantially to biliary secretory functions and bile transport. Although ErbB receptors have been widely studied in cholangiocarcino… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
38
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 58 publications
(44 citation statements)
references
References 76 publications
(164 reference statements)
1
38
1
1
Order By: Relevance
“…Treatment of CCA patients remains challenging despite the identification of molecular pathways with high therapeutic potential such as EGFR (5)(6)(7)27). Although antibodies or TKI against EGFR have shown efficacy in preclinical studies (27)(28)(29), they did not provide significant improvement of global survival in clinical trials in CCA (9)(10)(11)(12)(13)(14). Here, we highlight resistance mechanisms whereby CCA cells evade EGFR inhibition.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Treatment of CCA patients remains challenging despite the identification of molecular pathways with high therapeutic potential such as EGFR (5)(6)(7)27). Although antibodies or TKI against EGFR have shown efficacy in preclinical studies (27)(28)(29), they did not provide significant improvement of global survival in clinical trials in CCA (9)(10)(11)(12)(13)(14). Here, we highlight resistance mechanisms whereby CCA cells evade EGFR inhibition.…”
Section: Discussionmentioning
confidence: 96%
“…In addition, dysregulations of EGFR expression and signaling have been associated with tumor progression and poorer prognosis in CCA patients (7,8). However, despite EGFR attractive position as a molecular target for therapy, several independent clinical trials have reported very poor responses in patients with CCA treated with different small tyrosine kinase inhibitors (TKI) and monoclonal antibodies designed to specifically target EGFR (9)(10)(11)(12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…All these combinations showed enhanced inhibition both in vitro and in vivo. At the clinical level, anti‐EGFR therapies have been the most studied, either as single agents or in combination regimens . However, although they showed efficacy in preclinical studies, they did not provide significant improvement in overall survival in phases II and III clinical trials .…”
Section: Targeted Therapiesmentioning
confidence: 99%
“…At the clinical level, anti‐EGFR therapies have been the most studied, either as single agents or in combination regimens . However, although they showed efficacy in preclinical studies, they did not provide significant improvement in overall survival in phases II and III clinical trials . Interestingly, a recent phase Ib study showed longer median overall survival in iCCA patients treated with pulsatile erlotinib combined with chemotherapy compared to patients treated with standard chemotherapy alone, suggesting an effect for pulsatile administration of anti‐EGFR …”
Section: Targeted Therapiesmentioning
confidence: 99%